PENGARUH MENGGAMBAR IMAJINATIF BERBASIS CERITA BERGAMBAR TERHADAP PERKEMBANGAN KECERDASAN VISUAL SISWA SEKOLAH DASAR - Qonita, Ghisanahara Balqis; Amalia, Arsyi Rizqia; Maula, Luthfi Hamdani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of imaginative drawing activities based on picture stories on the visual intelligence of elementary school students. The research design used is Non-Equivalent Control Group Design. The sampling technique used is purposive sampling, with the research subjects being fifth grade students of Aisyiyah Elementary School, Sukabumi City, who were divided into two groups (experimental and control). The experimental class received treatment in the form of imaginative drawing activities with picture story stimuli, while the control class was given imaginative drawing activities based on keywords. The research instrument was a visual intelligence test conducted before and after the treatment (pretest and posttest). Data analysis was carried out using a paired sample t-test after fulfilling the prerequisite tests for normality and homogeneity. The results showed that the average pretest score of the experimental group was 57.17, increasing to 76.94 in the posttest. While the average score of the control group increased from 54.78 to 61.72. The results of the hypothesis test showed a significance value of 0.000 <0.05, which means that H0 is rejected and H1 is accepted. Thus, it can be concluded that imaginative drawing activities based on illustrated stories have a significant influence on the development of visual intelligence in elementary school students.